Perubahan Penghidupan Rumah Tangga Nelayan Tangkap Didaerah Aliran Sungai Indragiri (Kasus Desa Seberang Taluk) Kabuapten Kuantan Singingi Provinsi Riau - Mardona Mardona; Zulkarnain Zulkarnain; Darwis Darwis (Berkala Perikanan Terubuk, 2016)
This research was conducted on 26 January to 16 February 2016 in Seberang Taluk village of Kuantan Tengah Subdistrict at Kuantan Singingi Regency in Riau Province. Its was aimed to  identify the factor of changes in household livelihood of fishermen in Indragiri watershead and to assess the changes of household livelihood of fishermen in Indragiri watershead as well as to determine the relationship of the factors influencing the change of livelihood. The method used by survey methods, households have changed fisherman fishing livelihoods by seeking in sectors other than fisheries. Based on the research results can be explained that fishermen livelihoods changes caused by internal factors and exsternal. The change of which occurred significantly from the preparatory phase to the growth phase, Characteristics with real changes of fishermen household the livelihoods are age which have relationship with income and with the job opportunities,  are age which have relationship relationships  with sanitation, and hygiene, and the outpouring of working  hours relationships with food consumption.